1984
DOI: 10.1002/1097-0142(19841201)54:2+<2673::aid-cncr2820541412>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment alterntives: Head and neck cancers

Abstract: No tumor system is more amenable to multidiscipline therapy than head and neck cancers. Diagnosis is enhanced by fine-needle cytology, computerized tomography (a) scan, and tumor markers. Modified surgical techniques, COz laser, and immediate myocutaneous flap reconstruction have enhanced surgery. Endocurie therapy, radiosensitizers, and particle therapy supplementation have enhanced radiotherapy. Combination chemotherapy, immunotherapy, prostaglandin synthesis inhibitors, and retinoids have enhanced chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
4
0
1
Order By: Relevance
“…La quimioterapia sólo empezó a utilizarse formalmente en este tipo de tumores hacia los años 70s. Un artículo de la revista Cancer publicado en 1984 resume claramente que tipo de quimioterapias se solían utilizar y en qué escenarios clínicos (41). Para esa época, el metotrexate era el fármaco más estudiado, utilizado principalmente en CCyC de tipo escamoso recurrente (42).…”
Section: Quimioterapia En El Tratamiento Del Cáncer De Cabeza Y Cuellounclassified
“…La quimioterapia sólo empezó a utilizarse formalmente en este tipo de tumores hacia los años 70s. Un artículo de la revista Cancer publicado en 1984 resume claramente que tipo de quimioterapias se solían utilizar y en qué escenarios clínicos (41). Para esa época, el metotrexate era el fármaco más estudiado, utilizado principalmente en CCyC de tipo escamoso recurrente (42).…”
Section: Quimioterapia En El Tratamiento Del Cáncer De Cabeza Y Cuellounclassified
“…In the second half of the 20th century, chemotherapy gradually gained acceptance as a nonsurgical approach to cancer therapy (Watne 1984). Combinations of chemotherapy and radiation therapy were used increasingly for advanced-stage cancers, for both primary and adjuvant treatment.…”
Section: Evolution Of Therapy For Ohnsccmentioning
confidence: 99%
“…Early on, chemotherapy was not considered a frontline therapy for HNSCC. Chemotherapy often was reserved for palliative treatment (Watne 1984). Early experimental studies demonstrated the potential usefulness of intra-arterial chemotherapy in the palliative setting (Rogers 1964).…”
Section: Evolution Of Therapy For Ohnsccmentioning
confidence: 99%
“…In addition to the above, the geriatric patient presenting with cancer of the head and neck region constitutes slightly less than half of all oral cancers diagnosed (Schweiger and Salcetti, ). Cancers of this region are generally treated with surgery, radiation, chemotherapy or combinations of the three (Watne, ). The patients not only present with special problems due to their age but also with challenges resulting from treatment of their disease.…”
Section: Oral Biology Dental Technology and Dental Sciences; An Examentioning
confidence: 99%